The first thing you have to do is distribute the -
When you do that you get
5-x+3=2
Combine like terms
8-x=2
Subtract the 8
-x=-6
Divide by -1
x=6
2006-11-13 07:22:09
·
answer #1
·
answered by Shane 1
·
1⤊
0⤋
x=6
You want to distribute the minus sign outside the parentheses to the -3 that is inside. When you mulitiply two negatives together (in this case -1 and -3) you will always get a positive. Next you will move the x to the right side the equals sign so that it is a positve number. Combine the 5 and 3, and then move the 2 to the left side by subtracting it from each side to get 6.
5 -1(1x -3) = 2
5 - x +3 = 2
+x +x
5 + 3= 2 + x
8= 2 + x
-2 -2
6= x
2006-11-13 15:26:03
·
answer #2
·
answered by quatrapiller 6
·
0⤊
0⤋
5 - (x-3) = 2
Method 1
Well 5 - 3 = 2
So x - 3 = 3 Thus x = 6
Method 2
5 - x + 3 = 2
8 - x = 2
8 = 2 + x
x = 8 - 2
= 6
2006-11-13 15:23:24
·
answer #3
·
answered by Wal C 6
·
0⤊
0⤋
x=6
2006-11-13 15:22:15
·
answer #4
·
answered by Jon C 6
·
0⤊
0⤋
x=6
2006-11-13 15:21:40
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
x=6
2006-11-13 15:21:05
·
answer #6
·
answered by MALicious 3
·
0⤊
0⤋
x=6
5 - (x-3) = 2 subtract 5 from each side and your equation will look like this: -(x-3)=2-5 then you carry the - sign over to the x and the -3 which yields
-x+3 (remember 2 neg = pos)= -3
get the x by itself by subtracting 3 from each side and you'll have
-x = -3+-3 or -x = -6
but since x sign itself can't be negative x = 6
To check your answer insert 6 for x:
5-(6-3)=2
5-3=2
2=2
2006-11-13 15:37:59
·
answer #7
·
answered by SMS 1
·
0⤊
0⤋
5-(x-3) = 2
5 - x + 3 = 2
8 - x = 2
8 - x + x = 2 + x
8 = 2 + x
8 - 2 = 2 + x - 2
6 = x
x = 6
2006-11-13 15:22:43
·
answer #8
·
answered by bsk 2
·
0⤊
0⤋
5 - (x-3) = 2 distribut -1
5-x+3=2 subtract 8 from both sides
-x-2-8=-6 divide by -1
x=6
2006-11-13 15:37:53
·
answer #9
·
answered by yupchagee 7
·
0⤊
0⤋
5-x+3=2
x=6
2006-11-13 15:22:24
·
answer #10
·
answered by 7
·
0⤊
0⤋
5-x+3=2
-x=2-3-5
-x=-6
x=6
2006-11-13 15:22:20
·
answer #11
·
answered by -- 4
·
0⤊
0⤋